IMPLEMENTATION OF CHARACTER EDUCATION VALUES THROUGH DRAWING LEARNING IN ARTS AND CULTURE SUBJECTS AT SMP NEGERI 3 PADANGPANJANG - Sri Ulfa Idayanti; Iswandi (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2023)
Implementation of Character Education Values Through Drawing Learning in the Arts and Culture Subject at SMP Negeri 3 Padangpanjang is a process of instilling character education values contained in the image of the Garuda bird and being able to apply them to students' daily lives . The subjects in this research were students, subject teachers and teachers who taught general subjects among others; Religion, Pancasila and citizenship (KWN). This research aims to instill the values of character education through learning to draw the Garuda bird as the symbol of Indonesia and the character values contained therein in Cultural Arts subjects for Primary School students . Study this uses is method Mix Method . Data collection techniques with method observation , interviews , documentation and questionnaires . The results of the research show that implementing character education values through learning to draw Garuda birds can be used as a way to instill character education values in students. through material draw on the eyes lesson Art Culture . N values of character education found on the material draw Eagle covers value ; Religious , Honest , Responsible , Disciplined , Creative , Socially Concerned , Caring Environment , Tolerance , Work Loud , Independent , Democratic , Nationalism , Love for the Motherland, Friendly / Communicative and Passionate Nationality .